Evaluation of FMR1 gene mutations in Turkish women newly diagnosed with primary ovarian failure - Sarıkaya, Esma; Tokmak, Aytekin; Çakar, Esra Şükran; Güney, Gürhan; Düzkale, Neslihan; Özakşit, Müzeyyen Gülnur (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: One of the known causes of ovarian dysfunction is fragile X mental retardation gene 1 (FMR1) premutation. The prevalence of FMR1 premutation in primary ovarian failure (POF) cases may differ between the studies due to some reasons including POF definition, definition of premutation, and determination of study population, ethnicity, genetic and environmental factors. In this study authors aimed to determine the prevalence of FMR1 mutations in patients who applied to present clinic and diagnosed as POF. Methods: This retrospective cohort study was conducted on 200 women who had been newly diagnosed with POF in present clinic between 2013 and 2014. The presence of cytogenetic fragility was firstly investigated in all patients by using the lymphocyte culture method, and molecular analysis of the FMR1 gene was then performed. Genomic DNA’s of cases were isolated using standard protocols, followed by polymerase chain reaction amplification with an appropriate program. Fragment analysis of the amplification products were performed by agarose gel electrophoresis. Results: Cytogenetic analysis results in 200 cases were numerically and structurally normal in all patients, and as a result of molecular genetic analysis of FMR1 gene; 1 (0.5%) patient had complete mutation and 9 (4.5%) patients had premutation carriage. Conclusions: FMR1 gene mutations are common in women with POF. These mutations should be investigated in all patients presenting with POF, particularly in cases with early onset and family history of POF, and also genetic counseling should be given to those patients.